Self-Esteem and Happiness as Predictors of School Teachers’ Health: The Mediating Role of Job Satisfaction - Benevene, Paula; Ittan, Maya M.; Cortini, Michela (Frontiers in Psychology, 2018)
Background: A wealth of cross-sectional studies show consistent positive relationships between teachers’ happiness and self esteem on one hand, and health, on the other, which calls for additional research in order to disentangle cause and effect between the two, and to find potential mediators. Aims: To investigate the mediating role played by job satisfaction between teachers’ happiness and self esteem and their physical and mental health. Methods: A questionnaire was administered, containing questions about participants’ background information and the following scales: the Job Satisfaction Survey, the Rosenberg Self-Esteem Scale, the Physical and Mental Health Scales (SF12), and the Ivens Scale in the Adapted Version for Teachers: School Children’s Happiness Inventory (SCHI). The participants were 300 primary and middle school teachers from the Indian State of Kerala. Results: Job satisfaction fully mediates between both happiness and self esteem, and health in teachers. Conclusions: Work is a relevant domain to promote teachers’ happiness and self esteem, and their health, through job satisfaction.